معايير الجودة في بحوث علوم الإعلام والاتصال من منظور جودة التكوين للباحث الجزائري - دراسة إستطلاعية على عينة من الأساتذة الجزائريين- - حسيني, عمر; شوشان, زهرة (University of Eloued جامعة الوادي, 2021)
هدفت الدراسة للتعرف على معايير الجودة في بحوث علوم الإعلام والاتصال من منظور جودة التكوين للباحث الجزائري وقد جاءت هذه الدراسة في شكل دراسة إستطلاعية على عينة من الأساتذة الجزائريين، و تحديد أثر تلك المعايير من خلال الفروق في تلك المعايير التي تعود إلى متغيرات ( الجنس، الخبرة)، كما هدفت إلى تحديد أكثر فئات الباحثين تلقي الجودة التكوين في مجال بحوث الإعلام والاتصال، بالإضافة إلى التعرف على اقتراحات الباحثين للتغلب على الصعوبات التي قد تواجه الباحثين في مجال جودة التكوين للباحث الجزائري. تكونت عينة الدراسة من (70) أستاذ وأستاذة لديهم خبرة كافية في التدريس في الجامعة الجزائرية. وقد توصلت الدراسة إلى النتائج المتمثلة فيما يلي: - توجد فروق في نوعية الصعوبات التي تواجه الباحثين الجزائريين من وجهة نظرهم حسب متغير الجنس في مجال معايير الجودة. -لا توجد فروق في نوعية الصعوبات التي تواجه الباحثين الجزائريين في الجامعة من وجهة نظرهم حسب متغير الخبرة. - أبرز الصعوبات التي تواجه الباحثين الجزائريين في الجامعة تتمثل في مشكلة التكيف المهني ووالتدريس يوال بحثي مع البرامج الدراسية المستخدمة. ABSTRACT The study aimed to identify the quality standards in media and communication sciences research from the perspective of the training quality of the Algerian researcher. This study came in the form of an exploratory study on a sample of Algerian professors. And determining the effect of those standards through the differences in those criteria due to variables (gender, experience), It also aimed to identify the groups of researchers who receive the most training quality in the field of media and communication research, in addition to identifying researchers ’suggestions to overcome the difficulties that might face researchers in the field of training quality for the Algerian researcher. The study sample consisted of (70) professors with sufficient experience in teaching at the Algerian University. The study found the following results: - There are differences in the types of difficulties that Algerian researchers face, according to the gender variable in the field of quality standards. - There are no differences in the type of difficulties that Algerian researchers face at the university from their point of view, according to the experience variable. - The most prominent difficulties facing Algerian researchers at the university are the problem of professional, teaching and research adaptation to the study programs used.
Quality standards in media and communication sciences research from the perspective of the training quality of the Algerian researcher - An exploratory study on a sample of Algerian professors
الملتقى الدولي الافتراضي حول معايير الجودة في بحوث الإعلام والاتصال. 16-17 فيفري 2021 . كلية العلوم الاجتماعية والإنسانية.جامعة الوادي
Keywords: التكوين– جودة التكوين- بحوث الإعلام والاتصال; Training - Quality Training - Media and Communication Research